Problematic Internet Use Predicts Lesser Satisfaction with Life, but Psychological Distress Acts as a Mediator - Codina, Nuria; Pestana, José V; Ogden, Ruth; Wittmann, Marc; Martin-Soelch, Chantal; Witowska, Joanna; Černohorská, Vanda; Schoetensack, Christine; Papastamatelou, Julie; Klegr, Tereza; Chappuis, Sebastien; Fernandez-Boente, Monica; et al. (Cyberpsychology, behavior and social networking, 2025)
Problematic internet use (PIU) has emerged, from the extensive use of the internet, as a concept to describe and understand the more adverse influences of digitalization on people's experiences. PIU refers to compulsive or excessive internet use leading to psychosocial impairments (among others, anxiety, depression, lesser well-being), and it has been studied from diverse perspectives. However, the mechanisms through which PIU could exert its impact on broader satisfaction with life (SWL) remain unclear. The present work postulates that psychological distress acts as a mediator between PIU and SWL. This hypothesis is tested in large participant groups (N = 7,536), representative of the normative population of six European countries in terms of age and gender. In the context of full structural equation modeling, analyses of direct and indirect effects show evidence for partial mediation of psychological distress between PIU and SWL, with the small positive direct effect of PIU on SWL reversing its valence to moderate and negative via the mediation of psychological distress in all six countries. These findings show that psychological distress is relevant to consider both in trying to define the limits of PIU as a construct and in considering its impacts on SWL in general.
Keywords: depression; satisfaction with life; psychological distress; problematic internet use; anxiety; stress